2014
DOI: 10.3168/jds.2013-7582
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic mechanistic model of lactic acid metabolism in the rumen

Abstract: Current feed evaluation systems for ruminants are too imprecise to describe diets in terms of their acidosis risk. The dynamic mechanistic model described herein arises from the integration of a lactic acid (La) metabolism module into an extant model of whole-rumen function. The model was evaluated using published data from cows and sheep fed a range of diets or infused with various doses of La. The model performed well in simulating peak rumen La concentrations (coefficient of determination = 0.96; root mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
1
16
0
2
Order By: Relevance
“…In vivo studies are needed to evaluate the true effect of YHP on the pH of bovine rumen. It has been previously reported that the concentration of lactic acid rapidly rises in the bovine rumen after a meal, and is positively correlated with the proportion of CF in the meal (Counotte et al, 1983;Mills et al, 2014). Lactic acid was the first individual SCFA to rise also in the present study, as demonstrated by the 6 h time points of experiments 1 and 2 in which the proportion of lactic acid was 50-70% of the total SCFAs (Tables 1 and 4, respectively).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…In vivo studies are needed to evaluate the true effect of YHP on the pH of bovine rumen. It has been previously reported that the concentration of lactic acid rapidly rises in the bovine rumen after a meal, and is positively correlated with the proportion of CF in the meal (Counotte et al, 1983;Mills et al, 2014). Lactic acid was the first individual SCFA to rise also in the present study, as demonstrated by the 6 h time points of experiments 1 and 2 in which the proportion of lactic acid was 50-70% of the total SCFAs (Tables 1 and 4, respectively).…”
Section: Resultssupporting
confidence: 56%
“…In experiment 3, lactic acid was not detected at all. The results suggested that lactic acid was a transient metabolite, as is the case in bovine rumen in vivo (Mills et al, 2014). YHP further increased the lactic acid concentration in the 6-h time point from experiment 2 (P < 0.001; Table 4).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Reasons to distinguish functional classes of micro-organisms in rumen models are differences in the type of substrate fermented (type of carbohydrate in particular), the particular rumen niche they occupy with its own physical-chemical characteristics, e.g., retention time and acidity, and the specific role they exert that is related to the modeling aim; e.g., bacterial predation by protozoa and storage of polysaccharides (Dijkstra et al, 1992; Dijkstra, 1994; Figures 4A,B ) and rumen lactate metabolism (Mills et al, 2014). Mechanistic rumen models distinguish fibrolytic and amylolytic microbial activity because such a classification is well documented and in line with the distinct carbohydrate substrates for which intrinsic degradation characteristics are available.…”
Section: Introductionmentioning
confidence: 99%
“…These different states or responses might be due to a changed energy requirement for maintenance functions (Baldwin, 1995), or to regulatory mechanisms driven by changed availability of reduced co-factors (Van Lingen et al, 2016). With respect to representing the dynamics of inter-microbial relationships between various classes of micro-organisms, amongst the best documented and detailed models are the rumen protozoa metabolism model of Dijkstra (1994) and the rumen lactate metabolism model of Mills et al (2014). Some other additions to rumen models can be considered as model parameterization rather than addition of a functional class of micro-organisms if they do not include representation of the dynamics of this functional class and its inter-relationships with other classes.…”
Section: Introductionmentioning
confidence: 99%